The effect of hard infrastructure on perceived destination competitiveness: The moderating impact of mobile technology - Chiang Chan, Wei; May Chiun, Lo; Wan Hashim, Wan Ibrahim; Abang Azlan, Mohamad; Mohamad Kadim, Suaidi (Elsevier Science, Ltd., 2022)
Hard infrastructure is an important topic to research because of its importance to perceived destination competitiveness. Besides, tourism suppliers who adopt mobile technology can improve visitors' trip experiences. Moreover, Malaysia, is experiencing declined destination competitiveness ranking and poor hard infrastructure development in Sarawak. The primary goal of this research is to examine the hard infrastructures as determinants of perceived destination competitiveness and the moderating effect of mobile technology from the visitor's perspective. A total of 190 valid data were collected for further analysis. The data were analyzed using PLS-SEM approach. The result revealed that transportation and accommodation have a significant relationship with perceived destination competitiveness. Additionally, the relationship between telecommunication infrastructure and perceived destination competitiveness is moderated by mobile technology. The current study's findings aided scholars and practitioners by providing useful data backed up by empirical evidence on the moderating effect of mobile technology and the direct relationship between infrastructure and perceived destination competitiveness.